2003
DOI: 10.1023/a:1025810603241
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Patients sought their medication advice from a variety of sources and armed with this almost two thirds of patients wished to exercise their rights to be involved with their treatment planning. Sufficient discussion time appeared to be available to about half of the interviewees though only a few understood the intended benefits of prescribed corticosteroids used as an example in this work. A much better knowledge of drug side effects might have partly explained the high level of declared non-compliance. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 15 publications
1
12
2
Order By: Relevance
“…Numbers in parenthesis indicate percentage Accurate and well-planned oral education of patients by physicians and pharmacists improves the ability of patients to recall information and satisfy their needs for accurate and appropriate use of medication [5]. However, the present study and several previous studies [6,7] have shown that most patients are not provided with adequate and satisfactory oral or written instructions.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Numbers in parenthesis indicate percentage Accurate and well-planned oral education of patients by physicians and pharmacists improves the ability of patients to recall information and satisfy their needs for accurate and appropriate use of medication [5]. However, the present study and several previous studies [6,7] have shown that most patients are not provided with adequate and satisfactory oral or written instructions.…”
Section: Discussioncontrasting
confidence: 67%
“…The present study and several previous studies [6,7] have shown that most patients were not provided with Pharm World Sci (2008) 30:764-767 765 adequate and satisfactory oral or written instructions. A previous study showed that 66% of the patients were provided sufficient discussion time with their general practitioners (GPs) [7].…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Aboriginal Australians are the most disadvantaged sector of Australian society [6]. The enormous burden of OM in Australian Aboriginal children contributes to lifelong social disadvantage.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that between 25 and 80% of patients may receive conflicting information about their illness and its management (Blendon, Schoen, DesRoches, Osborn, & Zapert, 2003; Carpenter et al, 2010; Coleman, Smith, Raha, & Min, 2005), across diseases as diverse as cancer (Gray, Fitch, Phillips, Labrecque, & Klotz, 1999; Mills & Davidson, 2002), cardiopulmonary disease (Trewin & Veitch, 2003), rheumatic disease (Carpenter et al, in press, 2010; Lim et al, 2007), low back pain (McIntosh & Shaw, 2003), and mental illness (Pollock et al, 2004). Notably, patients most often receive conflicting information from two doctors (Carpenter et al, in press).…”
mentioning
confidence: 99%